The Implementation of Musyarakah by PT Bank Aceh Branch of Banda Aceh, Indonesia - Juli Andria; Darmawan Darmawan; Azhari Azhari (Faculty of Law, Sriwijaya University, Indonesia, 2019)
According to Article 19 Paragraph (1) of the Law Number 21 of 2008 concerning Sharia Banking, one of the activities of Sharia Banking is to provide financial funding based on musyarakah (profit sharing). The implementation of musyarakah by PT Bank Aceh Syariah in Banda Aceh has been covered up to 85 customers from the period of 2015 to 2017. In musyarakah contract the customers have to fulfil their obligations to pay the payments to the bank. However, the fact shows that the customers could not fulfil their obligations to pay their payments to the bank because they have income problems in running their businesses. From 2015 to 2017 there were seven customers were not well performed musyarakah. This condition has resulted in breach of contract by the customers which is known as non-performing musyarakah funding. This study aims to scrutinize legal consequences arising from non-performing musyarakah funding and identify the efforts taken in the settlement of this problem. This study is an empirical juridical research. Data required for this study were collected through field research by interviewing respondents or informants. The result shows that the legal consequences arising from this non-performing musyarakah funding were pledges or defaults by the customers because they violate the Article 12 of Musyarakah contract. The efforts taken in settling this problem among others are collecting the arrear obligations and handling non-performing musyarakah to the bank’s officer to be analysed based on legal analysis. Therefore, it is advised that the customers should fully fulfil their obligation to pay their payments to the bank based on musyarakah contract. Then, the bank officers are suggested to fully analyse the arrear obligations of the customers based on legal analysis. By doing so it could reduce non-performing musyarakah funding in the future